1998
DOI: 10.1073/pnas.95.18.10716
|View full text |Cite
|
Sign up to set email alerts
|

Tn 5 /IS 50 target recognition

Abstract: This communication reports an analysis of Tn5͞IS50 target site selection by using an extensive collection of Tn5 and IS50 insertions in two relatively small regions of DNA (less than 1 kb each). For both regions data were collected resulting from in vitro and in vivo transposition events. Since the data sets are consistent and transposase was the only protein present in vitro, this demonstrates that target selection is a property of only transposase. There appear to be two factors governing target selection. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
105
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(120 citation statements)
references
References 34 publications
14
105
0
Order By: Relevance
“…Libraries of 2 ϫ 10 5 independent insertion mutants were generated in E. coli strains MG1655 and DH10B using Tn5-based EZ::TNϽKAN-2ϾTnp transposome (Epicentre Technologies) as a transposon delivery system. It utilizes a mutant hyperactive form of the Tn5 transposase, which has been reported to have low insertion site specificity (41,64). In our study EZ::TN transposase was found to be sufficiently random to yield 1 to 14 independent insertions within a majority of E. coli genes (for example, see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Libraries of 2 ϫ 10 5 independent insertion mutants were generated in E. coli strains MG1655 and DH10B using Tn5-based EZ::TNϽKAN-2ϾTnp transposome (Epicentre Technologies) as a transposon delivery system. It utilizes a mutant hyperactive form of the Tn5 transposase, which has been reported to have low insertion site specificity (41,64). In our study EZ::TN transposase was found to be sufficiently random to yield 1 to 14 independent insertions within a majority of E. coli genes (for example, see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Afterward, transposon mutagenesis was performed on pDD365 using the EZ::TN In-Frame Linker Insertion Kit (Epicenter Technologies). This method relies on the ability of a modified 1000-bp Tn5 transposon element-coupled to transposase to insert itself randomly into target DNA in vitro (81,84). Transposon events are identified by kanamycin resistance.…”
Section: Methodsmentioning
confidence: 99%
“…To test this, two transposon-containing plasmids were used that differed only by the presence of outside end sequences in pRZTL1 and mosaic end sequences in pRZTL4. No significant differences were noted in transposition frequencies between the K40Q mutant and the hyperactive EKLP parent transposase with either form of the transposons; however, the transposition frequency using mosaic ends was about 10ϫ greater than using outside ends for both transposases (Table I, columns [3][4][5][6]. Based on these data, the 100ϫ difference in activity between these two transposase molecules observed in the in vivo mating out assay is due to a process that occurs in vivo not measured by the in vitro assay.…”
Section: In Vitro Excision Of Transposons By K40q Mutant Tn5mentioning
confidence: 99%
“…1 below). Genetic engineering of Tn5 transposase to generate a hyperactive form (EKLP) 1 and the optimization of the transposon end sequences allow many of the individual steps of the Tn5 transposition mechanism to be studied in vitro (1)(2)(3)(4)(5)(6). The hyperactive EKLP form of Tn5 transposase contains the mutations E54K, M56A, and L372P (4).…”
mentioning
confidence: 99%